2022
DOI: 10.3390/polym14194222
|View full text |Cite
|
Sign up to set email alerts
|

Experimental, Analytical, and Numerical Assessments for the Controversial Elastic Stiffness Enhancement of CFRP-Strengthened Timber Beams

Abstract: The strengthening of timber beams with carbon-fibre-reinforced polymers (CFRP) has been widely used in the last decades to enhance the behaviour of historical or new timber structures, usually for bending. While considerable improvement in capacity and ductility is typically achieved, the increase in stiffness was, in many cases, well short of analytical expectations, which tend to overestimate stiffness. This study addresses the problem by investigating the underlying mechanical behaviour using experimental, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In [8], the authors confirm an increase in stiffness by 13 % to 30 % for timber beams (45×45×1000 mm) reinforced with fabric-type carbon fibers on the lower face of the beam with a percentage of reinforcement of 0.268 % and 0.307 %, respectively. The increase in bearing capacity was recorded at the level of 27 %.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…In [8], the authors confirm an increase in stiffness by 13 % to 30 % for timber beams (45×45×1000 mm) reinforced with fabric-type carbon fibers on the lower face of the beam with a percentage of reinforcement of 0.268 % and 0.307 %, respectively. The increase in bearing capacity was recorded at the level of 27 %.…”
Section: Introductionmentioning
confidence: 77%
“…Research results showed an increase in the bearing capacity of reinforced beams from 28 % to 41 %. Works [8,9] focused on the research of fabric-type CFRP, which is rarely used in beams with a significant cross-section.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When subjected to bending loads, timber beams are relatively weak on the bottom side where high tensile stresses occur. Given this, FRP sheets are often adhesively bonded to the soffit of the timber beams to increase flexural stiffness, strength, ductility, and energy absorption as well as prevent premature failure of timber beams [11][12][13][14][15]. In this case, the FRP-timber bonded structures can exhibit various failure modes and damage mechanisms, which inherently depend upon several parameters, such as the timber strength, FRP sheets strength, bulk adhesive strength, adhesive-timber interface strength, and adhesive-FRP interface strength.…”
Section: Introductionmentioning
confidence: 99%